Isaiah among the ancient Near Eastern prophets : a comparative study of the earliest stages of the Isaiah tradition and the Neo-Assyrian prophecies - Jong, Matthijs J. de. (Vetus Testamentum, Supplements, 2007)
Focusing on the phenomenon of prophecy in the ancient Near East, this study offers a comparison between parts of First Isaiah and the Assyrian prophecies. In the first part, the material from First Isaiah and from seventh-century Assyria is investigated in its own right. The second part is a comparison of the Isaiah tradition in its earliest shape with the prophetic material from seventh-century Assyria. The topics dealt with in the comparison are the interrelation of prophetic oracles and historical events, the functions of the prophets, and the literary development of prophecy. The study shows that ancient Israelite prophecy, of which the historical Isaiah was an exponent, was much in conformity with ancient Near Eastern prophecy in general.